Challenges of the Social Economy Action Plan for Greece in the Light of the Socially Responsible Public Procurement - Lamprinidis, Lampros (Journal of Public Policy and Administration, 2023)
Purpose: The purpose of the Communication is to present the action plan for the social economy in the European Union. Public procurement is a powerful tool for public authorities to spend public money in an efficient, sustainable and strategic way, especially in times of budgetary constraints (EU Commission, 2017). Annual spending on public procurement in the EU amounts to â‚¬2 trillion, so managing it effectively can save significant resources for public budgets and investments, while supporting social and environmental policies. A public procurement strategy requires a change of attitude from public authorities, so that public procurement is no longer seen as a mere administrative process, but as a tool to serve broader objectives and needs, while respecting the rules governing the EU (EU Commission, 2017). With this in mind we will refer to the Action Plan for the Social Economy in the EU (2021) in the light of Socially Responsible Public Procurement in relation to Greece. Methodology: Concise review of the Action Plan for the Social Economy in EU in the Light of the Socially Responsible Public Procurement. For this reason, we will refer to Socially Responsible Public Procurement, European policies supporting the Social Economy, and the EU Action Plan for its development. Then we will refer to the Public Procurement Strategy in Greece from the point of view of supporting Social Economy Entities. Findings: Presentation of the challenges of the Public Procurement Strategy in Greece in relation to Socially Responsible Public Procurement and the Social Economy Action Plan by extension Unique Contribution to Theory Practice and Policy: The contribution of this paper is to inform stakeholders in Greece on the implementation of the Social Economy Action Plan of EU and its link to Socially Responsible Public Procurement. Through this link, the development of Social Economy Organisations can be supported on the one hand and on the other hand it can contribute to the sustainable development of the European economy and of Greece in particular.